Environmental Communication Strategy in Overcoming Cisadane River Water Pollution - Meisyanti Meisyanti; Khina Januar Rahmawati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Water is the most important component for humans to maintain their life, but pollution also occurs in water. One of the rivers that have been polluted is the Cisadane River which stretches from West Java to Banten. This case of Cisadane River pollution is one of the cases included in the environmental communication study, where the role of the stakeholders in it is needed. The unity of purpose to overcome Cisadane River pollution can be done in various ways, one of them is by implementing an environmental communication strategy. The purpose of this study is to analyze and identify environmental communication strategies in handling Cisadane River pollution that have been carried out by the Government and the Environmental Service of Tangerang City and South Tangerang City and to develop environmental communication strategies to overcome the problem of Cisadane River pollution. The research method was using descriptive qualitative with data collection techniques interviews, observation and Focus Group Discussion (FGD). The results of this study indicate that the environmental communication strategy carried out by the Government and the Environmental Service of Tangerang City and South Tangerang City in terms of the communication component has been running well. To make it even better, it needs the consistency in the management of the environmental communication. The development of an environmental communication strategy model uses transformational communication features by adding several things to the strategies that have been implemented by the City Government and the Environmental Service of Tangerang City and South Tangerang City. For implementation this strategy, they need to monitor, evaluate and the synergy between the provincial, city government and the Environmental Service and other services in each area traversed by the Cisadane River. Air menjadi komponen terpenting bagi manusia untuk mempertahankan kehidupannya, namun pencemaran juga terjadi pada air. Salah satu sungai yang tercemar adalah Sungai Cisadane yang terbentang dari Jawa Barat hingga Banten. Kasus pencemaran Sungai Cisadane ini merupakan salah satu kasus yang termasuk dalam kajian komunikasi lingkungan, di mana dibutuhkan peran dari stakeholder yang di dalamnya. Kesatuan tujuan untuk mengatasi pencemaran Sungai Cisadane ini bisa dilakukan dengan berbagai cara, salah satunya dengan menjalankan strategi komunikasi lingkungan. Tujuan penelitian ini adalah untuk menganalisa dan mengidentifikasi strategi komunikasi lingkungan dalam penanganan pencemaran Sungai Cisadane yang sudah dilakukan oleh Pemerintah Kota dan Dinas Lingkungan Hidup Kota Tangerang dan Kota Tangerang Selatan dan untuk mengembangkan strategi komunikasi lingkungan untuk mengatasi masalah pencemaran Sungai Cisadane. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data wawancara, observasi dan Focus Group Discussion (FGD). Hasil penelitian ini menyatakan bahwa strategi komunikasi lingkungan yang dijalankan oleh Pemerintah dan Dinas Lingkungan Hidup Kota Tangerang maupun Kota Tangerang Selatan ditinjau dari komponen komunikasi sudah berjalan dengan baik. Agar lebih baik lagi diperlukan konsistensi dalam pengelolaan strategi komunikasi lingkungan tersebut. Pengembangan model strategi komunikasi lingkungan menggunakan fitur komunikasi transformasional dengan menambahkan beberapa hal yang sudah dijalankan oleh Pemerintah Kota dan DLH Kota Tangerang dan Kota Tangerang Selatan. Dalam pelaksanaan strategi ini juga dibutuhkan monitoring, evaluasi dan perlu adanya sinergi antara pemerintah provinsi, kota maupun DLH dan dinas terkait lainnya pada setiap daerah yang dilintasi oleh Sungai Cisadane.